BUDAYA BANYUMAS SEBAGAI SUMBER BELAJAR IPS DI KABUPATEN BANYUMAS - Hidayat, Amin (Paramita: Historical Studies Journal, 2011)
Banyumas culture can be used as a source of learning for junior high students in the region Banyumas.Ã‚Â In addition to contributing significantly to the maintenance and preservation of local culture as an integral part of national culture, learning the IPS will be more meaningful for students.Ã‚Â Banyumas have the kinds of art, unique cultural traditions, and historical sites with very high philosophical and educational value.The types of art, tradition and history as a component or element of Banyumas Culture which is prominent and important to be appointed are: History of Banyumas, Tradition of Banyumas, Arts and Heritage of Banyumas .Ã‚Â Various alternative learning strategies can be chosen and applied social studies teacher in utilizing Banyumas Culture as a source of learning, one of them is, by applying contextual lear-ning model.Ã‚Â It is possible to still refer to the applicable curriculum, namely KTSP. Ã‚Â  Key words: culture, banyumas, IPS, SMP Ã‚Â